Impact of PDMAEMA Molecular Weight on Smart Properties of mPEG[44]-block-PDMAEMA - Shoulak, Brianna; Stubbs, Elizabeth; Conor, Phillip (My University, 2017)
The purpose of this study was to explore the benefits of using "smart" polymers to use in various applications, such as enhanced oil recovery and drug delivery.
Color poster with text, graphs, charts, and tables.
Keywords: PDMAEMA; Smart polymers; Polymers; Posters